STUDI KOMPARASI PIPA SCH 40 GALVANIZE DENGAN SCH 40 NON GALVANIZE PADA SISTEM PIPA BALLAST DIKAJI DARI SEGI TEKNIS DAN EKONOMIS - Jokosisworo, Sarjito (Department of Naval Architecture - Diponegoro University, 2010)
Vessel is an effective and efficient medium of sea transportation because it can transport goods in a large number. In planing and constructing the vessel, therefore, it is not only striven to be economical without decreasing its function, instruction of classification, and contruction power, but also simple to get the treatment. It will make the vessel more durable and the condition of equipment structure more stable to support the operation. One the important project and construction is to determine materials that will be used on the vessel. Pipe is a dominant component in operational system of each activator engine. Besides, it is as medium to transfer bold fluid and gas from a space to another space. Hence, it is important to protect the pipe from decreasing function which is caused by corrosion, so that damages the pipe. Considering the high vessel reparation fee, it is better to shade the pipe from the damages. The most efficient and the easiest protection and treatment to reduce corrosion in a pipe system is by using Galvanized method